Education and awareness raising activities of the British Society of Soil Science - Towers, Willie; Allton, Kathryn; Hallett, Steve (Cranfield University, 2014)
The British Society for Soil Science (BSSS) http://www.soils.org.uk is an international membership organisation and UK based charity committed to promoting the study and profession of soil science in its widest aspects. The Society is committed to reaching out to the public at large to educate and inform on the importance of soils to us all. The Society has adopted a range of approaches to soil education, tailored to the needs and aims of different audience types. We have developed the 'Working with Soil' initiative http://www.soilscientist.org/workingwithsoil which provides practicing soil scientists and potential funders with a set of professional competencies aligned to specific aspects of work. From 2013 The Society has developed a program of courses aligned to these documents aimed at meeting the professional development needs of those undertaking such work. So far these have focused on fundamentals of field characterisation, sampling and mapping which have been very well received, especially by early career practitioners who have had less exposure to field work. We have also produced posters and leaflets that demonstrate a range of soil functions which support human society, for example 'Soils in the City' and 'Soils of Britain'. These were originally developed in a more traditional formal style. The materials have also proved popular with local authorities, regional horticultural clubs and higher education establishments, notably agricultural colleges where they have been used to support student learning in both timetabled and project work. We have subsequently produced a further set of materials aimed at a much younger audience. We deliberately chose slightly quirkier names for these, for example 'Soils and Time Travel' and 'Soils and Spaceship Earth' as a hook to capture the child's imagination. These were designed by a specialist company who used a less formal language, the use of cartoons and alternative images and a wider range of font styles and sizes. This material has been distributed to all the secondary education schools in Great Britain, and receives very positive feedback from educators and pupils alike. The Society has also been highly visible at the BBC Summer of Wildlife roadshows over the summer of 2013. This involved a visual display of soils with two 'hands on' activities "What's in the Soil" and "Build your own Wormery". Each activity was supported with an A4 leaflet that people were able to take home or download from the website (www.soils.org.uk/education). The Society attended all four of the main roadshow events reaching an audience of more than 60,000 members of the public ranging in age from 1 to 100! The Society took to the live stage event during the Leeds show with CBCC "Wild" show presenters to talk about the formation of soils and the role of Earthworms. Some soil scientists who were very reticent about their involvement were actually very good at it and enjoyed it! So lets all get out there and do some more!